The effect of carbohydrate loading on physical performance and adaptations in amateur sports enthusiasts: A systematic review - Dewvi, Putu Ayu Savitri; Wulandari, Putu Ayu; Devi, Natasha Pradnya; Sumartini, Ni Ketut (Poltekkes Kemenkes Aceh, 2026)
Background: Carbohydrate loading (CL) increases muscle glycogen reserves before intense physical activity. While CL has been shown to be beneficial for elite athletes, the metabolic capacity and activity duration of amateur and recreational athletes are variable. As sports nutrition guidelines for amateur athletes vary, especially regarding CL indications, duration, and dose, this variance has practical and therapeutic ramifications.Objectives: This study aimed to systematically review the effects of carbohydrate loading on the physical performance and adaptation of amateur sports enthusiasts.Methods: This systematic review was conducted following the PRISMA 2020 guidelines. We searched PubMed, ScienceDirect, ProQuest, and Google Scholar for publications from 2005 to 2025. Experimental or randomized controlled trials of high-carbohydrate diets in non-elite athletes were included in this review. Two reviewers independently selected the articles, and a third reviewer resolved any disagreements. VO2max, time to exhaustion, race results, and metabolic responses were all recorded. The risk of bias and study quality were assessed using the Cochrane Risk of Bias 2.0 and the NIH Quality Assessment Tools.Results: Seven studies were included in the analysis. Five trials found that carbohydrate loading improved endurance and glucose stability and reduced fatigue. Events lasting > 90 min showed the greatest performance gains. Short-term and moderate-intensity activities had no meaningful impact on the two studies. These differences may have been caused by differences in training, glycogen storage, and diet.Conclusion: Carbohydrate loading improves endurance performance and metabolic efficiency, particularly during long-duration exercise. However, inter-individual heterogeneity emphasizes the need for tailored carbohydrate regimens to maximize athletic performance in endurance sports.